The Role of Sharia Crowdfunding in Poverty Reduction in Indonesia - Erizal Candra Efendi; Rozalinda; Nora Zulvianti (LP2M IAIN Palopo, 2025)
Poverty in Indonesia is still a significant problem with many people living below the poverty line. This study aims to analyze the role of sharia crowdfunding in reducing poverty by providing access to capital for micro and small businesses that are not accessible to conventional financial institutions. The research method used is a literature study, where secondary data is collected from various journals, articles, and publications related to sharia crowdfunding and poverty in Indonesia. The results of the study show that sharia crowdfunding platforms, such as Kitabisa.com, have succeeded in raising significant funds that contribute to poverty reduction by expanding access to funding and creating social solidarity in the community. However, challenges such as dependence on aid and verification of beneficiaries still need to be overcome so that the impact is more optimal. In conclusion, sharia crowdfunding has proven effective in helping to reduce poverty and strengthen the sharia economy in Indonesia, although improvements are needed in several aspects of its implementation.